Audiovisual LGTBIQphobia. The hiding of sexual diversity in Disney (Revista Apotheke, 2021)
LGTBIQphobia is a barrier to the normalization of sexually diverse groups. Products like Disney audiovisuals make this task difficult as the company tends to hide them. In this way the development of a more tolerant and respectful citizenship with the difference from the first ages is stopped. In education, there is a latent concern to eradicate LGBTI-phobic bullying. For this reason, through a queer positioning and a mixed methodology, the Disney “The Classics” collection is analyzed to manifest the attacks against this group and raise awareness among those who use it as a resource in their classrooms with groups of minors. Also to make visible the examples of sexual diversity designed in certain cartoons. As a consequence, it is concluded that it is a minority of Disney LGTB characters, and the relation with evil way. Offering a critical film reviews to teachers to use them correctly in their classrooms.
Keywords: LGTBIQphobia; Disney; cinematography; education; sexual diversity